Advantages and Disadvantages of Arbitration in the Context of International Law: Focus on Commercial and Ad Hoc Arbitration - Halimatusaddiah Siregar; Ardina Nur Inaya; Fahkry Wahyuda Siregar; M. Faiz Abdullah; Idham Khaliq Hasibuan (ISNU Sumatera Utara, 2024)
Arbitration has become a popular dispute resolution mechanism in international law, especially in the context of commercial and ad hoc arbitration. This study aims to evaluate the advantages and disadvantages of arbitration as an international dispute resolution method. Through literature analysis and case studies, it is found that commercial arbitration offers great flexibility, efficiency and privacy to the disputing parties. However, its high cost and sometimes slow process are significant drawbacks. On the other hand, ad hoc arbitration provides greater freedom in choosing the procedure and arbitrators, but the lack of formal structure may lead to uncertainty and difficulties in enforcement of the award. In conclusion, while arbitration provides an effective solution to international disputes, the choice between commercial and ad hoc arbitration should be carefully considered based on the specific needs of the parties. This study recommends strengthening the international framework to enhance the reliability of ad hoc arbitration processes.